Participatory design facilitates Person Centred Nursing in service improvement with older people: a secondary directed content analysis. Issue 9 (May 2017) - Wolstenholme, Daniel; Ross, Helen; Cobb, Mark; Bowen, Simon
Abstract : Aims and objectives: To explore, using the example of a project working with older people in an outpatient setting in a large UK NHS Teaching hospital, how the constructs of Person Centred Nursing are reflected in interviews from participants in a Co‐design led service improvement project. Background: Person Centred Care and Person Centred Nursing are recognised terms in healthcare. Co‐design (sometimes called participatory design) is an approach that seeks to involve all stakeholders in a creative process to deliver the best result, be this a product, technology or in this case a service. Co‐design practice shares some of the underpinning philosophy of Person Centred Nursing and potentially has methods to aid in Person Centred Nursing implementation. Research design: The research design was a qualitative secondary Directed analysis. Methods: Seven interview transcripts from nurses and older people who had participated in a Co‐design led improvement project in a large teaching hospital were transcribed and analysed. Two researchers analysed the transcripts for codes derived from McCormack & McCance's Person Centred Nursing Framework. Results: The four most expressed codes were as follows: from the pre‐requisites: knowing self; from care processes, engagement, working with patient's beliefs and values and shared Decision‐making; and from Expected outcomes, involvement in care. This study describes the Co‐design theory and practice that the participants responded to in the interviews and look at how the co‐design activity facilitated elements of the Person Centred Nursing framework. Conclusions: This study adds to the rich literature about using emancipatory and transformational approaches to Person Centred Nursing development, and is the first study exploring explicitly the potential contribution of Co‐design to this area. Implications for practice: Methods from Co‐design allow older people to contribute as equals in a practice development project, co‐design methods can facilitate nursing staff to engage meaningfully with older participants and develop a shared understanding and goals. The co‐produced outputs of Co‐design projects embody and value the expressed beliefs and values of staff and older people.